EFEKTIVITAS PEMANFAATAN KULTUR LOKAL DALAM BIOREAKTOR PENGOLAHAN AIR LIMBAH KERAJINAN ENDEK - Juliasari, Ni Made Tia; Budiarsa Suyasa, I Wayan; Rai, I Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 16 No 1 (2022)DO - 10.24843/EJES.2022.v16.i01.p03, 2022)
Endek is one of the fabrics that are in demand by local and foreign people. The distinctive pattern of this endek cloth continues to develop while still paying attention to the authenticity of the endek motives from Bali so that it is easily recognized by the public, however, in its production, it produces waste that causes environmental pollution therefore it needs to be managed. One of the easy and efficient textile waste management is a bioreactor by utilizing local culture. Local cultures are indicated as indigenous microorganisms originating from the waste itself. The purpose of this study is to analyze the effectiveness of local cultures in bioreactors in improving wastewater quality and analyze the effectiveness of using local microbial cultures in bioreactors for treating endek wastewater. This study applied a quantitative approach with experimental methods. The processing begins with the growth of biofilms to determine the biomass profile using the Mixed Liquor Suspended Solid (MLSS) method, then the color waste water is stored in an anaerobic reservoir for 24 hours then tested and then processing, later it is inundated for 1 hour before parameter measurement. The parameters tested were COD levels, color content and pH. Based on the results of the study, the optimum MLSS value obtained in the seeding process was 4490 mg/L on the 7th day and the biofilm growth biomass profile of 3240 mg/L on the 22nd day. The utilization of local microbial culture in the bioreactor in this study was effective in reducing the color content parameter by 77% at processing times of 384 and 408 hours, and decreasing pH was only effective at processing time of 6 hours and reducing COD was not effective. Keywords : endek wastewater, local culture, bioreactor, effectivenes